Effect combined learning on oral health self-efficacy and self-care behaviors of students: a randomized controlled trial - Zahra Sadat Hashemi; Mahboobeh Khorsandi; Mohsen Shamsi; Rahmatollah Moradzadeh (BMC, 2021)
Abstract Background In order to prevent oral diseases, the use of appropriate oral health education at childhood is one of the most important strategies for improving oral health knowledge and by extension positive oral health habits. Therefore, the present study aimed to evaluate the effect of animations and games as a strategy for improving oral health self-efficacy and self-care behaviors among 6-12-aged students. Methods In this interventional study, 82 students were selected based on cluster random sampling including 38 for the case and 44 for the control group. The case group received four sessions of combined learning per week including animations and games while the control group received routine school education. The data were collected in six domains including demographics, self-care, knowledge, attitude, behavior and self-efficacy before and 5 months after the intervention using a questionnaire. SPSS version 20 was used for data analysis. Results Five months after the intervention, the mean score of self-care, self-efficacy, behavior increased from 3.8 to 4.8, 36.8 to 48.9, and 17.07 to 18.29, respectively indicating a significant change (p < 0.05). However, no significant change was reported in these variables in the control group (p  > 0.05). Conclusion The use of animation combined with other strategies for oral health self-care education can positively influence the students' performance and self-efficacy. IRCT registration number This trial was registered at IRCT. IRCT2017042133565N1 Registration date: 2017-05-17 https://en.irct.ir/trial/25851